Pre-treatment and inoculum affect the microbial community structure and enhance the biogas reactor performance in a pilot-scale biodigestion of municipal solid waste. (March 2018) - Ventorino, Valeria; Romano, Ida; Pagliano, Giorgia; Robertiello, Alessandro; Pepe, Olimpia
Highlights: The relationship between microbial communities and biogas production was considered. Methane was formed primarily via the hydrogenotrophic pathway. Mechanical pretreatment and inoculum increased and accelerated methane production. Abstract: During anaerobic digestion of municipal solid waste, organic matter is converted to methane, carbon dioxide, and other organic and inorganic compounds through a complex cooperation among different microbial groups with different metabolic activities. Here, culture-dependent and independent approaches provided evidence for examining the relationship between bacterial and archaeal communities and methane production in a pilot-scale anaerobic digestion. The abundance of aerobic and anaerobic functional groups of C and N cycles, such as cellulolytic, pectinolytic, amylolytic and proteolytic bacteria, was high at the beginning of the experiment and was drastically decreased after anaerobic digestion. In contrast, the ammonifiers increased in the biogas producing reactors in a higher pH environment. The methanogenic archaeal genera recovered were Methanobrevibacter, Methanobacterium, Methanoculleus and Methanocorpusculum, thus indicating that methane was formed primarily by the hydrogenotrophic pathway in the reactors. Moreover, the mechanical pretreatment effects, as well as the effect of pelleted manure as inoculum, were considered. The highest methane production was detected in the biodigesters with minced organic waste, thus indicating that pre-treatment of a heterogeneous starting matrix was essential for improving biogas production and stabilizing the process.